Derivacion Implicita2
Derivacion Implicita2
Derivacion Implicita2
3
𝑦= 5𝑥 2
𝑥 2 + 𝑦 2 = 25
𝑥 2 + 𝑥𝑦 + 𝑦 2 = 3
𝑑𝑦
𝑑𝑥 𝑛 ′
𝑓 𝑥
𝐷𝑥 =
𝑚
𝑓(𝑥)𝑛 = 𝑚𝑚
𝑦 = 2𝑥 + 5 ∴ 𝑦 ′ = 2 𝑓(𝑥)(𝑚−𝑛)
3 ′
1(10𝑥) 10𝑥
𝑦= (5𝑥 2 ) ∴ 𝑦 = 3
= 3
3 5𝑥 2 2 3 5𝑥 2 2
𝑥 2 + 𝑦 2 = 25 ∴ 𝑦 2 = 25 − 𝑥 2 ∴ 𝑦 = 25 − 𝑥 2 ∴ 𝑦 ′
1 −2𝑥 −2𝑥 𝑥
= = =−
2 25 − 𝑥 2 2 25 − 𝑥 2 25 − 𝑥 2
𝑥 2 + 𝑥𝑦 + 𝑦 2 = 3
𝑥 2 + 𝑥𝑦 + 𝑦 2 = 3 ∴ 𝑥𝑦 + 𝑦 2 = 3 − 𝑥 2 ∴ 𝑦 2 = 3 − 𝑥 2 − 𝑥𝑦
∴ 𝑦 = 3 − 𝑥 2 − 𝑥𝑦
3 − 𝑥2 − 𝑦2
𝑦=
𝑥
•
•
𝑥 2 + 𝑦 2 = 25 𝑥 2 + 𝑥𝑦 + 𝑦 2 = 3
2𝑥 + 2𝑦𝑦 ′ = 0 2𝑥 + 𝑦 1 + 𝑥 1 𝑦 ′ + 2𝑦𝑦 ′ = 0
2𝑦𝑦 ′ = −2𝑥 2𝑥 + 𝑦 + 𝑥𝑦 ′ + 2𝑦𝑦 ′ = 0
′
2𝑥 𝑥 𝑥𝑦 ′ + 2𝑦𝑦 ′ = −2𝑥 − 𝑦
𝑦 =− =−
2𝑦 𝑦 𝑦 ′ 𝑥 + 2𝑦 = −2𝑥 − 𝑦
′
𝑥 −2𝑥 − 𝑦
𝑦 =− ′
𝑦 =
𝑦 𝑥 + 2𝑦
𝑦 = 25 − 𝑥 2
′
𝑥
𝑦 =−
25 − 𝑥 2 −2(1) − 2 −2 − 2 4
𝑦′ = = =−
1 + 2(2) 5 5
2 3
𝑥 + 𝑦 − 2𝑦 = 3
2𝑥 + 3𝑦 2 𝑦 ′ − 2𝑦 ′ = 0
3𝑦 2 𝑦 ′ − 2𝑦 ′ = −2𝑥
′ 2 ′
2𝑥 ′
4
𝑦 3𝑦 − 2 = −2𝑥 ∴ 𝑦 = − 2 ∴ 𝑦 = − = −4
3𝑦 − 2 1
𝒚 − 𝒚𝟏 = 𝒎 𝒙 − 𝒙𝟏
𝒚 − 𝟏 = −𝟒 𝒙 − 𝟐
𝑦 = −4𝑥 + 9
𝒚 − 𝒚𝟏 = 𝒎 𝒙 − 𝒙𝟏
3 3
𝑥 + 𝑦 = (6𝑥)(𝑦)
3𝑥 2 + 3𝑦 2 𝑦 ′ = 𝑦 6 + 6𝑥 1 𝑦′
2 2 ′ ′
3𝑥 + 3𝑦 𝑦 = 6𝑦 + 6𝑥𝑦
2 ′ ′ 2
3𝑦 𝑦 − 6𝑥𝑦 = 6𝑦 − 3𝑥
𝑦 ′ 3𝑦 2 − 6𝑥 = 6𝑦 − 3𝑥 2
𝟐 2 𝟐
′
𝟔𝒚 − 𝟑𝒙 3(2𝑦 − 𝑥 ) ′
𝟐𝒚 − 𝒙
𝒚 = 𝟐
= 2
∴𝒚 = 𝟐
𝟑𝒚 − 𝟔𝒙 3(𝑦 − 2𝑥) (𝒚 − 𝟐𝒙)
𝟐
′
𝟐(𝟑) − 𝟑 𝟔−𝟗 𝟑
𝒚 = 𝟐 = = − = −𝟏
(𝟑 − 𝟐(𝟑)) 𝟗 − 𝟔 𝟑
𝒚 − 𝟑 = −𝟏 𝒙 − 𝟑
𝑦 = −𝑥 + 3 + 6 ∴ 𝒚 = −𝒙 + 𝟔
𝒅𝒚
𝒅𝒙
𝐷 𝑢𝑣 = 𝑣𝑑𝑢 + 𝑢𝑑𝑣
4 2 3
𝑥 𝑦 3
𝑥 𝑦 2𝑥𝑦
4 3 𝑢 = 𝑥 3 𝑑𝑢 = 3𝑥 2 𝑢 = 2𝑥 𝑑𝑢 = 2
𝑢 = 𝑥 𝑑𝑢 = 4𝑥
𝑣 = 𝑦 2 𝑑𝑣 = 2𝑦𝑦′ 𝑣 = 𝑦 𝑑𝑣 = 𝑦′ 𝑣 = 𝑦 3 𝑑𝑣 = 3𝑦 2 𝑦′
5
𝑃 + 2 (𝑉 − 0.03) = 9.7
𝑉
𝑑𝑉
𝑑𝑃
5
𝑥 + 2 (𝑦 − 0.03) = 9.7
𝑦
(𝑥 + 5𝑦 −2 )(𝑦 − 0.03) = 9.7
(𝑥 + 5𝑦 −2 )(𝑦 − 0.03) = 9.7
𝑢 = 𝑥 + 5𝑦 −2 ∴ 𝑑𝑢 = 1 − 10𝑦 −3 𝑦′
𝑣 = 𝑦 − 0.03 ∴ 𝑑𝑣 = 𝑦′